Jan Bill, Bjørn Poulsen, Flemming Rieck og Ole Ventegodt: Dansk søfarts historie, I: Indtil 1588. Red. Ole Feldbæk m.fl. (Gyldendal, 1997). 287 s., 388 kr. - Ladewig Petersen, E. (Historie/Jyske Samlinger, 1998)
-